Antibiotic use in Australian and Swedish primary care: a cross-country comparison. (2nd January 2022) - Andersson, Konny; van Driel, Mieke; Hedin, Katarina; Hollingworth, Samantha; Merlo, Gregory
Abstract: Objective: Antimicrobial resistance is a growing worldwide problem and is considered to be one of the biggest threats to global health by the World Health Organization. Insights into the determinants of antibiotic prescribing may be gained by comparing the antibiotic usage patterns of Australia and Sweden. Design: Publicly available data on dispensed use of antibiotics in Australia and Sweden between 2006 and 2018. Medicine use was measured using defined daily dose per 1, 000 inhabitants per day (DDD/1000/day) and the number of dispensed prescriptions per 1000 inhabitants (prescriptions/1000). Results: The use of antibiotics increased over the study period in Australia by 1.8% and decreased in Sweden by 26.3%. Use was consistently higher in Australia, double that of Sweden in 2018. Penicillin with extended spectrum was the most used class of antibiotics in Australia followed by penicillin with beta lactamase inhibitors. In Sweden, the most used class was beta lactamase-sensitive penicillin and the least used class was penicillin with beta lactamase inhibitors. Conclusion: Antibiotic use in Australia is higher than in Sweden, with a higher proportion of broad-spectrum penicillin, including combinations with beta lactamase inhibitors, and cephalosporins. Factors that may contribute to these differences in antibiotic use include differences in guidelines, the duration of national antimicrobial stewardship programs, and differences in funding mechanisms. Key points: Australia has had a consistently higher dispensed use of antibiotics compared to Sweden from 2006 to 2018; and up to twice the use in 2018 A higher proportion of dispensed antibiotics in Australia were broad-spectrum penicillin, including combinations with beta lactamase inhibitors, and cefalosporins. The most commonly used class of antibiotics in Australia is penicillin with extended spectrum, compared to beta lactamase sensitive penicillin in Sweden. Use of macrolides, sulphonamides and trimethoprim, cephalosporins, penicillin with beta lactamase inhibitors and penicillin with extended spectrum was consistently higher in Australia, whereas in Sweden use of fluoroquinolones, lincosamides, beta lactamase-resistant penicillin and beta lactamase sensitive penicillin was higher. The observed differences could be explained by antibiotic choice recommended in guidelines, prevalence of point-of-care testing, models of primary care funding, the presence and duration of national antimicrobial stewardship programmes, and cultural differences.